Degradation of an HDPE geomembrane without HALS in chlorinated water. Issue 4 (7th August 2019) - Abdelaal, F. B.; Rowe, R. K.
Abstract : The degradation of a 1.5 mm high-density polyethylene geomembrane without hindered amine light stabilizers (HALS) immersed in four chlorinated water solutions is examined over a 3-year period at five temperatures (25, 40, 65, 75, and 85°C). To simulate field conditions in potable water reservoirs in which high successive chlorine doses are introduced into the system, the field mass loading of the chlorine was simulated in the laboratory instead of the more typical constant average chlorine concentration. The solutions had a boosted free chlorine content selected to maintain the same ratio of the mass of free chlorine in the water to the surface area of the geomembrane in the immersion jars, as experienced in field applications, for four nominal free chlorine concentrations (content of 0.5, 1.0, 2.5, and 5.0 ppm). The depletion of antioxidants and decrease in stress crack resistance (SCR) for a geomembrane immersed in a solution with 0.5 ppm free chlorine was much faster than in deionised and tap waters or synthetic municipal solid waste leachate. At this concentration, the geomembrane reached complete brittleness after 6 months of incubation at 85°C. Arrhenius modelling is used to predict the length of the antioxidant depletion stage and the time to brittleness (reaching SCR = 50 h) in chlorinated water.